Intrapersonal Communication of Gen Z Women Who Choose to Marry Below the Ideal Age - Justine Terence Putri; M. Denu Poyo; Budhi Waskito (Indonesian Journal Publisher, 2026)
This study aims to analyze the intrapersonal communication of Generation Z women who choose to marry before the ideal age. This phenomenon is interesting because, amidst the tendency of Gen Z to delay marriage due to education, career, and economic considerations, some women still choose to marry before the age of 21. The study used a qualitative approach with phenomenological methods. Informants consisted of Gen Z women who married before the ideal age and supporting informants from the DAMAR Lampung Association. Data collection techniques were conducted through in-depth interviews, observation, and documentation. Data analysis used thematic analysis. The results indicate that the decision to marry is formed through the process of decoding experiences, integrating information, utilizing past memories, encoding the meaning of marriage, feedback from the social environment, and various distractions that influence thought processes. Intrapersonal communication is a key factor that helps informants define their own readiness and build confidence in their decision to marry. This research contributes to the development of intrapersonal communication studies in the context of young women's decision-making.